DINAMIKA RAGAM SUMBER PENDAPATAN RUMAH TANGGA PEDESAAN MISKIN DI JAWA TENGAH - Suprapti Supardi; Sri Marwanti (Universitas Sebelas Maret, 2006)
Impecunious Rural spreading in rural of Central Java cover various area with immeasurable nature resource potency with impecunious countryside proportion reach 28,71%. this research aim to study manner of source of earnings of impecunious rural house hold in Central Java with determined research location by purposive, and data analysis with discriptive statistics